STRATEGI GURU KELAS MEMOTIVASI SISWA KELAS VI UNTUK MELAKSANAKAN SALAT DUHA DI SD NEGERI 18 SADAYAN Laili Khainur ** - Laili Khainur; Suhari, Sera Yuliantini (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
The study of this research is the class teacher’s strategy to motivate class VI students to carry out the duha prayer at SD Negeri 18 Sadayan fot the 2022-2023 academic year. The aim is to describe the class teacher’s strategy planning to motivate class VI students to carry out the duha prayer. Describe the implementation of the class teacher’s strategy to motivate students to perform the duha prayer. Describe the supporting and inhibiting factors of the class teacher’s strategy to motivate class VI student’s to perform the duha prayer. The approach used is qualitative with a type of phenomenology. Data collection techniques use observation, interviews, and documentation. Data analysis techniques use data reduction, data display, and verivication. The data validity checking technique uses triangulation and member check. The result is a strategic plan for the class teacher to motivate class VI students to carry out duha prayers including gradual habituation, starting habituation and continuous habituation. The implementation of the class teacher’s strategy to motivate class VI students to perform the duha prayer includes increasing the ability to memorize the reading of the duha prayer and improving the ability to practice the duha prayer. Supporting factors and inhibiting factors for the class teacher’s strategy to motivate class VI students to carry out the duha prayer, namely supporting factors: school principal, students. Inhibiting factors: facilities and infrastructure